(1)H, (13)C and (15)N resonance assignments for the microtubule-binding domain of the kinetoplastid kinetochore protein KKT4 from Trypanosoma brucei - Ludzia, Patryk (Biomol NMR Assign, 2020)
KKT4 is a kinetoplastid-specific microtubule-binding kinetochore protein that lacks significant similarity to any known kinetochore or microtubule-binding proteins. Here we present the (1)H, (13)C and (15)N resonance assignments for several fragments from the microtubule-binding domain of KKT4 (KKT4(115–343)) from Trypanosoma brucei. These assignments provide the starting point for detailed investigations of the structure, dynamics and interactions of the microtubule-binding region of KKT4. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12104-020-09968-1) contains supplementary material, which is available to authorized users.